Real-life effectiveness of canakinumab in cryopyrin-associated periodic syndrome - Kümmerle-Deschner, Jasmin; Blank, Norbert (Rheumatology, 2016)
Abstract. Objective. Cryopyrin-associated periodic syndrome (CAPS) is a heterogeneous group of diseases characterized by excessive IL-1β release resulting in s